Gender-Based Violence at Workplace: The Nigerian Experience - Okebiorun, J. O.; Oluwakemi, Ojeomogha Tawakalitu (NIU Journal of Humanities, 2022)
This study investigated Gender-Based violence at workplace in Nigeria. The study adopted the descriptive survey type of research design. The sample for the study consisted of 395 respondents randomly selected from ten (10) companies in two industrial estates in Lagos and Ogun states of Nigeria. The instrument used for data collection for the study was the questionnaire titled â€˜Gender-Based Violence Questionnaireâ€™ (GBVQ) which produced a reliability index of 0.824. Data collected was analysed using descriptive statistical techniques and the weighted mean score of 2.5 as a criterion mean score for decision. The hypotheses were analysed with ANOVA and Pearson moment of correlation. The study revealed that there is a positive and significant relationship between women protection law in restraining gender-based violence in workplace in Nigeria. The study also showed a positive and significant relationship between Adult Education and its programmes in fighting Gender-based violence in workplace in Nigeria (r-values = 0.  P 70.05 since P = .000). Based on the result of the findings, it was recommended that both government and employers of labour should eliminate all forms of violence against women through reactivation of gender and equal opportunities bills and labour laws in Nigeria. Keywords: Gender-Based, violence, workplace, Adult Education, women and Nigeria.